A comparative study of COVID-19 responses in South Korea and Japan: political nexus triad and policy responses. (September 2021) - Jae Moon, M.; Suzuki, Kohei; Park, Tae In; Sakuwa, Kentaro
Korea and Japan, neighboring democratic countries in Northeast Asia, announced their first COVID-19 cases in January 2020 and witnessed similar patterns of disease spread but adopted different policy approaches to address the pandemic (agile and proactive approach versus cautious and restraint-based approach). Applying the political nexus triad model, this study analyzes and compares institutional contexts and governance structures of Korea and Japan, then examines the differences in policy responses of the two Asian countries. This study first reviews the state of COVID-19 and examines changes in the conventional president-led political nexus triad in Korea and the bureaucracy-led political nexus triad in Japan. Then, this study examines how the differences in institutional contexts and governance structures shaped policy responses and policy outcomes of the two countries in managing the COVID-19 crisis. Points for practitioners:   Institutional and governance structure in a society are likely to affect policymaking processes as well as selection of policies among various policy alternatives.   Government officials often need to refer to government capacity as well as citizens' voluntary participation in resolving wicked policy problems like COVID-19.   Policy decisions made by government officials affect policy outcomes while political environment and political leadership are equally important to policy effectiveness.